Data from: Evaluation of the ontogeny and sexual dimorphism in a new species of Middle Triassic Darwinulocopina (Crustacea, Ostracoda) from Argentina - Carignano, Ana Paula (2020)
The data comprises the linear measurements (length, width and heigth in microns) and the Procrustes coordinates in lateral and dorsal views of the carapaces of the Darwinulocopina Prasuchonella huarpe (Middle Triassic, Cerro de las Cabras Formation, Cuyana Basin, Province of Mendoza, Argentina). The carapaces used for the study are housed at the Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales (IANIGLA), CCT-CONICET-Mendoza, Argentina, under the acronym IANIGLA-PI.